2017
DOI: 10.1016/j.envres.2017.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of total and source-specific particulate air pollution on incident cardiovascular disease in Gothenburg, Sweden

Abstract: The main PM air pollutants were associated with ischemic heart disease and stroke (in women) at the relatively low exposure levels in Gothenburg, Sweden. The associations tended to be stronger for women than for men, for non-smokers than for smokers, and for higher socioeconomic classes than for lower. The associations could not be attributed to a specific PM source or type, and differed somewhat between the two cohorts. The results of this study confirm that further efforts to reduce air pollution exposure sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 49 publications
7
91
2
1
Order By: Relevance
“…After assessing 58 full‐text for eligibility; we excluded nine studies because of: (1) no PM 2.5 data for the hypertension outcome ( n = 3), (2) increments for the pollutant concentration was change from previous concentration/place ( n = 2), (3) no clear data on hazard ratio, only in a diagram without precise data on hazard ratio and confidence interval ( n = 1), and (4) no specific data on pollutants, only distance from highways/road ( n = 3) (Figure 1). We included 49 articles in qualitative and quantitative synthesis; 5 articles were a joint cohort studies comprising of 2 (Dehbi 2017), 2 (Stockfelt 2018), 3 (Cai 2018), 11 (ESCAPE 2014), and 22 (Beelen 2014) cohorts, adding up to a total of 84 cohorts 1,3,5‐7,9‐52 . There were a total of 28 215 394 subjects from 84 cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After assessing 58 full‐text for eligibility; we excluded nine studies because of: (1) no PM 2.5 data for the hypertension outcome ( n = 3), (2) increments for the pollutant concentration was change from previous concentration/place ( n = 2), (3) no clear data on hazard ratio, only in a diagram without precise data on hazard ratio and confidence interval ( n = 1), and (4) no specific data on pollutants, only distance from highways/road ( n = 3) (Figure 1). We included 49 articles in qualitative and quantitative synthesis; 5 articles were a joint cohort studies comprising of 2 (Dehbi 2017), 2 (Stockfelt 2018), 3 (Cai 2018), 11 (ESCAPE 2014), and 22 (Beelen 2014) cohorts, adding up to a total of 84 cohorts 1,3,5‐7,9‐52 . There were a total of 28 215 394 subjects from 84 cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting finding was the association of HF with PM 10 , but not with PM 2.5 . Five cohorts investigate PM 2.5 and four studies for PM 10 and its association to HF 5,11,34,48 . After the removal of Atkinson et al study from the PM 10 pool, the analysis was based on the same four cohorts, and the HR became more significant.…”
Section: Discussionmentioning
confidence: 99%
“…In MESA Air, Kaufman et al found that women may have an increased CAC progression due to long-term exposure to PM 2.5 compared to men [10••]. Additionally, stronger associations between long-term exposure to PM with incident ischemic heart disease, stroke, heart failure and atrial fibrillation were noted among women compared to men even at relatively low levels of exposures in Gothenburg, Sweden [98]. Similarly, women were reported to have increased CVD mortality compared to men due to short-term exposure to PM 10 and SO 2 in Hefei, China [97].…”
Section: Sociodemographics (Age Sex Racial/ethnic Minorities and Lomentioning
confidence: 99%
“…Henschel et al (2012) have examined intervention studies focusing on improvements in air quality and associated health benefits for the assessed population. Some studies have focused on trends and effects associated with particulate matter (Tang et al, 2014;Keuken et al, 2011;Correria et al, 2013), and some studies have also included ozone (Fann and Risley, 2013;Gramsch et al, 2006). Correria et al (2013) estimated that for the most urban communities in the USA, as much as 18 % of the increase in life expectancy from 2000 to 2007 was attributable to the reduction in PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%